Experimental and numerical studies on hysteretic behavior of a novel bending-friction coupled damper. (February 2023) - Lu, Yujie; Lv, Qingfang; Sun, Tongfei; Liu, Ye; Tang, Hongyuan
Abstract: A novel bending-friction coupled damper (BFCD), capable of providing stable energy dissipation and improved stiffness against multi-level earthquakes, is proposed in the present study. To investigate the influences of loading protocols and configurations of bending bars on the hysteretic behavior of the BFCD, quasi-static tests were conducted on one conventional friction damper and five BFCD specimens. Three processes during each loading cycle, i.e., the static friction process, the sliding friction process and the coupled working process, were clearly reflected by the test hysteretic curves. Attributed to the adoption of bending bars, the maximum forces of all specimens increased by 98.0%–153.7% compared with the sliding friction forces. The BFCDs adopting linear-shaped bending bars presented higher strength, stiffness and energy dissipation compared with those adopting the partially weakened bending bars. The cumulative energy dissipation per volume of partially weakened bending bars with a slightly weakened diameter was 31.8% larger than that of linear-shaped bars, which showed a higher material utilization ratio. In addition, finite element models of BFCDs were established and validated. Configuration improvements were conducted to achieve a more stable and controllable behavior of the BFCD. Numerical parametric analyses based on the improved BFCD model confirmed that the strength, stiffness and the activation sequence of two damping parts could be effectively controlled through reasonable design. Highlights: Proposal of a novel bending-friction coupled damper (BFCD). Quasi-static tests on one conventional friction damper and five BFCDs. Parametric analyses on the BFCD based on a refined 3-D solid numerical model.